IMPACT OF EU INITIATIVES ON SOCIAL ECONOMY AND PUBLIC PROCUREMENT IN GREECE: A COMPREHENSIVE STUDY OF LEGAL AND POLICY FRAMEWORKS - Karavas, Sophia A (Top Journal of Public Policy and Administration (TJPPA), 2023)
This study explores the impact of European Union (EU) initiatives on the Social Economy and Public Procurement in Greece, providing a comprehensive analysis of the legal and policy frameworks in place. The EU’s Action Plan for the Social Economy serves as a central focus, emphasizing the pivotal role of Public Procurement in efficiently and sustainably allocating public funds, particularly in times of budgetary constraints. With an annual expenditure of €2 trillion on public procurement within the EU, this study underscores the potential for substantial resource savings in public budgets while aligning with social and environmental objectives. A critical aspect of the research is the transformation of public procurement from a mere administrative process into a strategic tool that serves broader societal goals while adhering to EU regulations. By examining the EU’s Socially Responsible Public Procurement (SRPP) approach, this study highlights the significance of including social aspects in procurement processes, such as employment opportunities, social inclusion, and sustainability criteria. The study delves into Greece’s Public Procurement Strategy, focusing on its alignment with socially responsible public procurement practices and its implications for supporting Social Economy Entities. It identifies challenges in Greece’s public procurement strategy concerning SRPP and its correlation with the EU’s Social Economy Action Plan. This research contributes to informing stakeholders in Greece about the implementation of the EU’s Social Economy Action Plan and its interconnectedness with socially responsible public procurement. The study’s findings not only offer insights into supporting the development of Social Economy Organizations in Greece but also contribute to the sustainable economic growth of both Greece and the broader European context